Mortality after liver surgery in Germany. Issue 11 (24th July 2019) - Filmann, N; Walter, D; Schadde, E; Bruns, C; Keck, T; Lang, H; Oldhafer, K; Schlitt, H J; Schön, M R; Herrmann, E; Bechstein, W O; Schnitzbauer, A A
Abstract: Background: Mortality rates after liver surgery are not well documented in Germany. More than 1000 hospitals offer liver resection, but there is no central regulation of infrastructure requirements or outcome quality. Methods: Hospital mortality rates after liver resection were analysed using the standardized hospital discharge data (Diagnosis-Related Groups, ICD-10 and German operations and procedure key codes) provided by the Research Data Centre of the Federal Statistical Office and Statistical Offices of the Länder in Wiesbaden, Germany. Results: A total of 110 332 liver procedures carried out between 2010 and 2015 were identified. The overall hospital mortality rate for all resections was 5·8 per cent. The mortality rate among 17 574 major hepatic procedures was 10·4 per cent. Patients who had surgery for colorectal liver metastases (CRLMs) had the lowest mortality rate among those with malignancy (5·5 per cent), followed by patients with gallbladder cancer (7·1 per cent), hepatocellular carcinoma (9·3 per cent) and intrahepatic cholangiocarcinoma (11·0 per cent). Patients with extrahepatic cholangiocarcinoma had the highest mortality rate (14·6 per cent). The mortality rate for extended hepatectomy was 16·2 per cent and the need for a biliodigestive anastomosis increased this to 25·5 per cent. Failure to rescue after complications led to mortality rates of more than 30 per cent in some subgroups. There was a significant volume–outcome relationship for CRLM surgery in very high-volume centres (mean 26–60 major resections for CRLMs per year). The mortality rate was 4·6 per cent in very high-volume centres compared with 7·5 per cent in very low-volume hospitals (odds ratio 0·60, 95 per cent c.i. 0·42 to 0·77; P < 0·001). Conclusion: This analysis of outcome data after liver resection in Germany suggests that hospital mortality remains high. There should be more focused research to understand, improve or justify factors leading to this result, and consideration of centralization of liver surgery. Graphical Abstract: Mortality following liver surgery has been analysed using data from the Federal Statistical Office from 2010 to 2015. Overall mortality in more than 100 000 resections was 5·8 per cent, and that after major resections was 10·4 per cent. A volume–outcome relationship was evident after major resections for colorectal liver metastases (CRLMs) in centres performing more than 25 major resections per year, with the mortality rate decreasing from more than 6·5 per cent to 4·6 per cent. DRG, Diagnosis-Related Groups; ECC, extrahepatic cholangiocarcinoma; BDA, biliodigestive anastomosis. Case for centralilzation of liver surgery